Kano Model Kepuasan Pengguna Lulusan Fakultas Teknologi Industri Universitas Kristen Petra - Shierly Jayapranata; Jani Rahardjo (Jurnal Titra, 2014)
This study was conducted to determine the categorized of users satisfaction on the performance of Faculty of Technology alumni. Fifty alumni were randomly chosen across national companies. Performance assessment based on nine attributes namely integrity, professionalism, English proficiency, information technology, communication skill, leadership and organization, teamwork, self development, and creativity and innovation. The users scored these indicators via questionaries. The result shows that the “Must Be” skills need to be owned by the alumni are self-development, English proficiency, leadership and organization.